Clinical Outcomes of Patients with Multiple Myeloma Presenting with Renal Failure - Vasant, Joydeep Singh; Gupta, Naveen; Malhotra, Hemant; Godara, Suraj; Yadav, Ajay; Kumbhaj, Prashant; Punia, Ankur; Soni, Priyanka; Sharma, Lalit Mohan (South Asian Journal of Cancer, 2025)
Aims and Objective This article studies the clinical outcome of patients with multiple myeloma who have renal failure at presentation.Methodology Patients with multiple myeloma presenting with serum creatinine of more than or equal to 2 mg/dL from outpatient department at Sri Ram Cancer Centre, Mahatma Gandhi Medical College & Hospital, Jaipur, Rajasthan, India, were screened for baseline serum creatinine and estimated glomerular filtration rate (eGFR). Assessment was done at completion of 6 months from diagnosis—patients' clinical condition, renal response (serum creatinine and eGFR), and disease response as per the International Myeloma Working Group criteria.Results Final response assessment was done at a follow-up of 6 months. Half of the patients achieved a renal complete response; the highest being in the lenalidomide group (83.3%). Patients with eGFR < 15 mL/min/m2 at presentation fared poorly versus those with eGFR > 15 mL/min/m2. Patients who were dialysis-dependent at baseline had poorer renal responses as compared with those who were dialysis-independent. Out of six patients who were initially dialysis-dependent, four (66.6%) became dialysis-independent after treatment.
Keywords: creatinine; dialysis; light chain; multiple myeloma; renal failure